Enhanced 2,3-Butanediol production by mutant Enterobacter ludwigii using Brewers’ spent grain hydrolysate: process optimization for a pragmatic biorefinery loom - Amraoui, Yassin; Prabhu, Ashish A.; Narisetty, Vivek; Coulon, Frederic; Chandel, Anuj Kumar; Willoughby, Nicholas; Jacob, Samuel; Koutinas, Apostolis; Kumar, Vinod (Elsevier, 2021)
2,3-Butanediol (BDO) is a fossil-based versatile bulk chemical with a multitude of applications. BDO can also be synthesized using microbial cell factories harnessing renewable feedstocks. However, the high cost of the substrate via microbial route impedes commercial manufacturing of BDO. Therefore, identification of cheaper substrates could make bio-based BDO production more cost-competitive. Brewers’ spent grain (BSG), a major by-product of breweries, is an inexpensive source of fermentable sugars and proteins. In the present study, we have attempted the bioproduction of BDO by Enterobacter ludwigii using BSG as feedstock. A random E. ludwigii mutant obtained after treatment with ethyl methane sulfonate (EMS) resulted in a BDO titer (9.5 g/L), ~30% higher in comparison to the wild type strain with a yield of 0.48 gBDO/gGlucose approaching the theoretical yield of 0.50 gBDO/gGlucose. The enzymatic hydrolysis of microwave-assisted alkali pretreated BSG was optimized using the statistical Taguchi design. The BSG hydrolysis under optimal conditions (pH: 6.0; temperature: 50 °C; BSG: 10% w/v; enzyme loading: 2% v/v) resulted in a glucose yield of 0.25 gGlucose/gBiomass. The uncontrolled pH was found to be more beneficial for BDO accumulation from BSG hydrolysate in batch bioreactor cultivation as compared with controlled one. The fed-batch cultivation with forced pH fluctuations at an aeration rate of 2.0 vvm resulted in BDO accumulation of 118.5 g/L from glucose-rich BSG hydrolysate with the yield and productivity of 0.43 g/g and 1.65 g/L.h, respectively. To the best of our knowledge, this is the first study on BDO production from BSG.
Keywords: 2,3-Butanediol; Glucose-rich BSG hydrolysate; Enzymatic hydrolysis; Brewers’ spent grain; Random mutagenesis; Enterobacter ludwigii